Pengaruh Brand Awareness, Brand Loyalty, dan Brand Image terhadap Keputusan Pembelian Produk Kosmetik - Prissiani Andi Ningrum; Adi Masliardi; Rena Augia Putrie; Susti Rumianti; Ma'rifani Fitri Arisa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
With the development of the era, cosmetics have become an important need, especially for women. This is because women always want to look beautiful and attractive when doing activities and often meet many people. The use of cosmetics is done to support appearance. This study aims to determine the Influence of Brand Awareness, Brand Loyalty and Brand Image on Cosmetic Purchasing Decisions. By using quantitative descriptive research methods, sample determination using the lemeshow formula with 100 respondents, sampling using the Purposive Sampling Technique. The data collection technique uses a Questionnaire which is then processed using IBM SPSS 25. The findings in this study are Brand Awareness, Brand Loyalty and Brand Image have a positive and significant effect on cosmetic purchasing decisions.